Avaliação comparativa dos efeitos gastrointestinais e renais do trometamol, cetoprofeno e diclofenaco de sódio em ratos - LIMA, Mariana Souza de (2019)
The Nonsteroidal anti-inflammatory drugs (NSAIDs) are often used to control pain, fever and inflammation. Although the benefits obtained from the use of NSAIDs are important, around 25% of people who use such drugs have side effects, which limit their use. From this principle, the study aimed to evaluate the gastrointestinal and renal side effects after the use of anti-inflammatory Trometamol, and compare with the most commonly used anti-inflammatory drugs: Ketoprofen and Diclofenac Sodium. The type of study used to resolve the problem was an experimental comparative applied. Sub chronic doses of the drugs were administered in 28 Wistar rats divided into 4 groups. We analyzed stomach ulcer index, blood count and creatinine tests and histopathological analyzes of renal structure. The Trometamol and Ketoprofen were drugs that caught more attention when we see the graphics, because their rates of minor damage were higher in most graphics (RBCs, ulcer index, platelets and leukocytes). The difference between the four experimental groups was not large, so the medicines may be used at doses sub-chronic during a period of 15 days, without causing severe side effects. However, the problems caused per these drugs are proven and users of NSAIDs should always be alert to a possible damage to the body. However, these medicine were shown that they can cause serious damage to the gastrointestinal and renal systems.